2012
DOI: 10.3945/jn.111.150052
|View full text |Cite
|
Sign up to set email alerts
|

Apo-10′-Lycopenoic Acid, a Lycopene Metabolite, Increases Sirtuin 1 mRNA and Protein Levels and Decreases Hepatic Fat Accumulation in ob/ob Mice3

Abstract: Lycopene has been shown to be beneficial in protecting against high-fat diet-induced fatty liver. The recent demonstration that lycopene can be converted by carotene 9',10'-oxygenase into a biologically active metabolite, ALA, led us to propose that the function of lycopene can be mediated by ALA. In the present study, male ob/ob mice were fed a liquid high-fat diet (60% energy from fat) with ALA supplementation (ALA group, 240 μg · kg body weight(-1) · d(-1)) or without ALA supplementation as the control (C g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 57 publications
(54 reference statements)
5
53
1
Order By: Relevance
“…All changes obtained in rats after 4 weeks of being fed with HFD are reported in results, and have been repeatedly found in previous studies, [16][17][18][19][20][21][22]25 and allowed us to properly assay the therapeutic efficacy of ND plus LYC against ND alone.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…All changes obtained in rats after 4 weeks of being fed with HFD are reported in results, and have been repeatedly found in previous studies, [16][17][18][19][20][21][22]25 and allowed us to properly assay the therapeutic efficacy of ND plus LYC against ND alone.…”
Section: Discussionsupporting
confidence: 54%
“…[9][10][11][12] Potential health benefits of lycopene (LYC) have been studied for more than 75 years. 7,13,14 In particular, experimental studies have shown that LYC supplementation effectively prevents the development of various liver injuries 15 : Animals were fed during several weeks with a high-fat diet (HFD) and supplemented with LYC, [16][17][18] an LYC metabolite, 16,19,20 or tomato juice as a source of LYC, 21,22 to prevent diet-mediated steatosis, 16,18,22 diethylnitrosamine-initiated HFD-promoted hepatocarcinoma, 17,19,20 and a metabolic pattern from an HFD. 21 The aim of this study was to assess the ability of LYC to return liver steatosis and to revert hepatic morphological changes produced by an HFD.…”
Section: Introductionmentioning
confidence: 99%
“…BCO2 metabolizes lycopene through asymmetric cleavage at the 9#,10# double bond and generates metabolites, which include apo-10#-lycopenal, apo-10#-lycopenol, and apo-10#-lycopenoic acid (APO10LA; chemical structure shown in Supplemental Figure 1) (12,13). Evidence suggests that these metabolites may exhibit more important biological roles than lycopene itself (9,14,15), and BCO2 ablation in mice altered lycopene metabolism (16,17). In particular, APO10LA supplementation was effective in inhibiting hepatic steatosis in genetically induced obese (ob/ob) mice (15) and attenuating high saturated fat diet (HSFD)-induced liver inflammation as well as tumor number and volume in C57Bl/6J mice (18).…”
Section: Introductionmentioning
confidence: 97%
“…Evidence suggests that these metabolites may exhibit more important biological roles than lycopene itself (9,14,15), and BCO2 ablation in mice altered lycopene metabolism (16,17). In particular, APO10LA supplementation was effective in inhibiting hepatic steatosis in genetically induced obese (ob/ob) mice (15) and attenuating high saturated fat diet (HSFD)-induced liver inflammation as well as tumor number and volume in C57Bl/6J mice (18). An important question remains as to whether the biological activity of lycopene could be different from its metabolite APO10LA in the absence of BCO2 expression.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, it was reported that apo-10 ′ -lycopenoic acid led to the increase in SIRT1 enzyme activity by treatment with this metabolite in ob/ob mice, resulting in prevention of fatty liver ( 99 ). In this study the compound was fed in the diet at 40 µg/g diet (or 240 µg/kg body weight /day).…”
Section: Biological Activities Of Apolycopenoidsmentioning
confidence: 99%